Impact of the covid-19 pandemic on tax pressure (Gestionar: revista de empresa y gobierno, 2021)
This paper addresses the various companies that are formalized whose taxes have an impact on ensuring and affecting income to the public treasury, for which the objective is to determine how the post-crisis of COVID 19 affects the collection of tax on income. income from micro and small businesses. This analysis arose from the estimate of SUNAT itself, before the pandemis it estimated that in our country around 50% is evaded in indirect taxes, 30% in direct taxes. For the processing of the information of the surveys, first highlighting that it is correlational with a quantitative approach, of a non-experimental cross-sectional design, because the collection of information was in a single moment, later making known the situation of collections from the perspective of the taxpayers, for this study a stratified probabilistic sample of companies in the Puno region was chosen, 300 companies belonging to the MYPE tax regime as a sample. Obtained as a result, in which the shows that there is a median relationship with r = 0.619, which means that the impact caused by the pandemic in the future regarding the tax pressure is of outstanding importance. Likewise, there is a regular adaptation to the new reality, which results in the low payment of taxes where r = 0.343, in addition, companies show a regular acceptance of the payment of taxes due to the economic reduction and business volatility and finally there is a High positive relationship between the post-COVID 19 crisis and tax pressure with 0.704, with a significance level of 0.00 less than 0.05.
Keywords: tax pressure; income tax; post-crisis; market volatility; SUNAT